2 μm Passively Q-switched all-solid-state laser based on WSe2 saturable absorber. (May 2019) - Cao, Lihua; Tang, Wenjing; Zhao, Shengzhi; Li, Ying; Zhang, Xiaodong; Qi, Na; Li, Dechun
Highlights: WSe2 -SA employed in a solid-state Q-switched laser at 2 μm firstly. Obtained the shortest pulse duration in 2 μm based on 2D material SAs. Obtained the largest peak power in 2 μm based on WSe2 -SA. Show the potential to generate high-quality pulse laser of WSe2 -SA. Abstract: Based on a high-quality WSe2 film prepared by the ultrasound-assisted liquid phase exfoliation (UALPE) method, a passively Q-switched all-solid-state Tm:YLF laser at 2 μm with high peak power was presented. The laser characteristics versus the pump power were investigated experimentally. Under the pump power of 8.84 W, the maximum single pulse energy of 12.8 μJ and peak power of 30 W were obtained, corresponding to the perfect pulse duration and maximum repetition rate of 427 ns and 82 kHz, respectively. To the best of our knowledge, it is the first presentation of WSe2 -SA employed in a solid-state Q-switched crystalline laser at 2 μm.